2021
DOI: 10.1016/j.stemcr.2021.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine signaling regulates oligodendroglial cell genesis from SVZ precursor cells

Abstract: Neural and oligodendrocyte precursor cells (NPCs and OPCs) in the subventricular zone (SVZ) of the brain contribute to oligodendrogenesis throughout life, in part due to direct regulation by chemokines. The role of the chemokine fractalkine is well established in microglia; however, the effect of fractalkine on SVZ precursor cells is unknown. We show that murine SVZ NPCs and OPCs express the fractalkine receptor (CX3CR1) and bind fractalkine. Exogenous fractalkine directly enhances OPC and oligodendrocyte gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 49 publications
2
45
0
1
Order By: Relevance
“…In cuprizone‐treated animals, CC‐3 expression was not increased in CC‐1+ cells, suggesting that the decrease in mature oligodendrocytes in mice with defective fractalkine signaling is a result of aberrant cell differentiation as opposed to cell death mechanisms (Figure 3). Together, these data suggest that fractalkine signaling indirectly influences oligodendrogenesis, and are consistent with recent literature showing the involvement of fractalkine in the regulation of oligodendrogenesis and development (Voronova et al, 2017; Watson et al, 2021).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In cuprizone‐treated animals, CC‐3 expression was not increased in CC‐1+ cells, suggesting that the decrease in mature oligodendrocytes in mice with defective fractalkine signaling is a result of aberrant cell differentiation as opposed to cell death mechanisms (Figure 3). Together, these data suggest that fractalkine signaling indirectly influences oligodendrogenesis, and are consistent with recent literature showing the involvement of fractalkine in the regulation of oligodendrogenesis and development (Voronova et al, 2017; Watson et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…The observation of increased NG‐2+ cells in hCX3CR1 I249/M280 mice point to an unexplored area regarding the use of FKN as an effective mediator for the interaction of new oligodendrocytes to enhance remyelination and repair. Watson, et al reported that exogenous fractalkine directly enhanced OPC and oligodendrogenesis in vitro, and the inhibition of endogenous fractalkine signaling reduced oligodendrocyte formation without causing an upregulation in CC‐3+ cells (Watson et al, 2021). Similarly, we did not detect an increase in CC‐3+ cells in CC‐1+ mature oligodendrocytes; however, our data do not exclude the possibility of other cell death mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8c). This notion is supported by the presence of Olig2expressing NSCs in the ventricular zone of the medial ganglionic eminence (MGE) as early as E9.5 82 and cerebellum at E10.5 142 , Olig2 + PDGFRɑ + OPCs in the subventricular zone of the MGE 143 , and the sparse number of oligodendrocytes identified in a Glast lineage-tracing study 144 .…”
Section: Discussionmentioning
confidence: 97%
“…Through RNA profiling, immunoinhibitory proteins involved in microglial homeostatic regulation, such as the CD200 receptor and CX 3 CL1, have been observed to have decreased expression in aged mice [ 90 , 91 ]. CD200 and CX 3 CL1 are exclusively expressed by microglia in the CNS, with their corresponding ligands expressed in neurons and oligodendrocytes [ 92 , 93 ]. Following the removal or inhibition of these proteins, it was demonstrated that the characteristics of microglia from aged mice were restored to those exhibited in young microglia [ 90 , 94 , 95 ].…”
Section: Microglial Cell Function In An Aging Populationmentioning
confidence: 99%